Delayed spontaneous traumatic pneumocephalus - Chandran, T.H.; Prepageran, Narayanan; Philip, Rajan; Gopala, K.; Ahmad Zubaidi, A.L.; Jalaludin, M.A. (Malaysian Medical Association, 2007)
Pneumocephalus or collection of air in the intracranial cavity can occur after trauma or surgery. However, delayed pneumocephalus occurring months after the initial injury is not common. We would like to report a case of spontaneous traumatic pneumoencephalocele presenting with transient recurrent hemiparesis 14 months after the initial trauma.